India's Foreign Policy : dilemma over nonalignment 2.0 - Tripathi, Sudhanshu (Thousand Oaks : SAGE Publishing, 2020)
"India's Foreign Policy Dilemma over Non-Alignment 2.0 presents the story of India's quest for renewed focus on the doctrine of Non-Alignment. It begins with a discussion on the evolution of India's Foreign Policy along with the origin of its most important pillar, Non-Alignment, and its cumulative effect in India and abroad. It further discusses challenges, compulsions and constraints for India's Foreign Policy in context of the current instability and insecurity due to mounting Chinese and Pakistani collusion against India's rising profile in Asia, the emerging Pyongyang-Beijing-Moscow axis against the US, the evolving US-China bipolar world order in the background of eastward shifting geopolitics, economic recession and terrorism. The book argues that it is incumbent upon India to take a fresh lead today to reinvent the doctrine not only for its own national interests but also for the entire Third World. It proposes various steps to revitalize India's Foreign Policy so that India can play a desired role in the present global order"--
Keywords: India -- Diplomatic relation -- Nonalignment